Optimization of a nonlinear amplifying loop mirror for amplitude regeneration in phase-shift-keyed transmission - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
We present the numerical optimization of the transmission characteristics of a nonlinear amplifying loop mirror for amplitude regeneration of phase-encoded optical transmission formats. Adjusting the splitting factor, the amplifier gain and the phase bias, minimal phase distortions can be achieved while strong amplitude fluctuations are regenerated. The limiting effects of noise from the built-in amplifier and of amplified Rayleigh backscattering are also discussed. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.optimi
Keywords: 2R-regeneration; All-optical regeneration; Differential phase-shift keying; Nonlinear amplifying loop mirror